Jendrassik maneuver effect on spinal and brainstem reflexes - (:unkn) unknown (SPRINGER, 2019)
The effect of Jendrassik Maneuver (JM) has been extensively studied on monosynaptic reflexes in numerous muscles below the level at which the maneuver was performed. Here we hypothesize that the effect of JM could be observed also on other reflexes, indicating a widespread influence of performing a motor act such as the JM. We examined polysynaptic reflexes caudal (i.e., the withdrawal reflex of the lower extremities) and rostral (i.e., the blink reflex to supraorbital nerve stimulation) to the level of JM contraction. We have assessed soleus tendon (T) reflex; withdrawal reflex in tibialis anterior and soleus muscle; blink reflex (BR), blink reflex excitability recovery curve (BR-ER) and prepulse inhibition of the blink reflex. Our results showed that (1) T-reflex amplitude increased during JM and decreased just after and 15 min after JM; (2) no change in the withdrawal reflex; (3) R2 area of BR reduced significantly just after or 15 min after JM; (4) Prepulse inhibition in BR reduced significantly during JM; (5) no change in BR-ER. Our results indicate that JM leads to generalized effects on neural excitability at both caudal and rostral levels. Furthermore, JM has a selective effect on excitability of reflex circuitries.
Keywords: Jendrassik maneuver; Tendon reflex; Brainstem reflexes; Monosynaptic; Polysynaptic reflexes; BLINK REFLEX; PREPULSE INHIBITION; PARKINSONS-DISEASE; EXCITABILITY; MUSCLE; REINFORCEMENT; THRESHOLD; RESPONSES; CHOREA